2019
DOI: 10.3390/rs11172019
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Persistence and Regenerative Zones in Coastal Forests Triggered by Sea Level Rise and Storms

Abstract: Retreat of coastal forests in relation to sea level rise has been widely documented. Recent work indicates that coastal forests on the Delmarva Peninsula, United States, can be differentiated into persistence and regenerative zones as a function of sea-level rise and storm events. In the lower persistence zone trees cannot regenerate because of frequent flooding and high soil salinity. This study aims to verify the existence of these zones using spectral remote sensing data, and determine whether the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…A pulse disturbance can have severe impacts on a landscape, causing widespread plant mortality as well as geomorphic change. However, if conditions return to their previous state after the pulse, upland plant communities can likely recover and the total amount of land cover change is likely to be small (Fagherazzi, Nordio, et al, 2019). However, gradual presses can change landscape conditions and prevent recovery after a pulse disturbance.…”
Section: The Biophysical Processes Governing the Marsh‐upland Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…A pulse disturbance can have severe impacts on a landscape, causing widespread plant mortality as well as geomorphic change. However, if conditions return to their previous state after the pulse, upland plant communities can likely recover and the total amount of land cover change is likely to be small (Fagherazzi, Nordio, et al, 2019). However, gradual presses can change landscape conditions and prevent recovery after a pulse disturbance.…”
Section: The Biophysical Processes Governing the Marsh‐upland Boundarymentioning
confidence: 99%
“…Sea level rise will trigger ecosystem shifts in wetlands, with salt marshes transgressing in upland areas (Fagherazzi, Anisfeld, et al, 2019; Fagherazzi, Nordio, et al, 2019) and, in warm climates, mangroves replacing salt marshes at the marine edge (Saintilan et al, 2014). The migration of marshes into uplands changes the ecosystem services that humans obtain from coastal landscapes (Feagin et al, 2010; Schmidt et al, 2014).…”
Section: Implications For Management and Restoration Of Salt Marshesmentioning
confidence: 99%
“…As depicted in Figure 5a, the comparison of the pre-and post-oil-spill status of the vegetation area showed a general decrease in vegetation health with respect to 15 of the indices. However, the NDWI after oil pollution shows an increase in value, which is likely due to the high absorption and presence of surface water that changed over time [63,93]. Further analysis with the use of paired T-Test (Table 9) indicated that nine of the fifteen indices that reflect deterioration in post oil spill vegetation health (RVI, CVI, GCI, GNDVI, NDVI, MSI, MDWI, SARVI2 and SAVI) were statistically significant with p-value < 0.05.…”
Section: Oil Spill Pollution Impact Assessment On Vegetation and Wetlandmentioning
confidence: 99%
“…Marsh migration into retreating upland forests is considered to be primarily controlled by the local rate of SLR and the slope of adjacent uplands (Brinson et al, 1995; Kirwan, Temmerman, et al, 2016). However, the pace and mechanisms of ecosystem change are likely controlled by a more complex interplay between gradual SLR and episodic events (Fernandes et al, 2018; Fagherazzi, Anisfeld, et al, 2019; Fagherazzi, Nordio, et al, 2019; Schieder and Kirwan, 2019). Soils and herbaceous vegetation respond quickly (Anisfeld et al, 2017), but the extent of mature forests may lag behind SLR (Kirwan et al, 2007; Williams et al, 1999).…”
Section: Introductionmentioning
confidence: 99%